Perceptions of Risk Factors and Complications of Obesity in Female Medical Students of South India: A Cross-Sectional Study - Yerpude, Pravin N; Jogdand, Keerti S (Disease and Health Research - New Insights Vol. 1, 2024)
Aim: The present study aimed to find out the extent of the problem of obesity and to assess the subjects’ awareness of risk factors and complications of obesity. Introduction: The World Health Organisation has described obesity as one of the most neglected public health issues. Initially, obesity was only a problem in high-income countries; however, at present, it is rising in middle and low-income countries as well, rapidly in India. Globally, non-communicable diseases are increasingly recognized as a major cause of morbidity and mortality. The countries of the Southeast Asia region are facing a double burden, with a heavy load of infectious diseases and an increasing burden due to non-communicable diseases. The growing prevalence of non-communicable diseases, especially in emerging nations like India, poses a challenge to the already overburdened healthcare system. Non-communicable diseases include a variety of illnesses, with obesity being a more frequent cause. Materials and Methods: The present cross-sectional study was carried out in November 2012. The study was conducted among all 1st and 2nd year female MBBS students of Katuri Medical College, Guntur (Andhra Pradesh). Height and weight were measured using the standard procedures suggested by Jelliffe. Body Mass Index was computed using the formula [weight in (kg) / height (m2)]. Results: Using the BMI cut-off points, the findings revealed that 23.30 % of study subjects were overweight and 12.50 % of study subjects were obese. When the girls were asked about factors contributing to obesity, an overwhelming majority (85.80%) of the subjects attributed diet to obesity. As far as psychosocial problems are concerned, nearly 59.66 of the subjects mentioned low self-esteem as a complication related to obesity. Obesity is known to increase the risk of various diseases and awareness of them is the first step towards taking steps to prevent this. While a high level of awareness is present among medical students regarding major complications of obesity but for other complications, they should also get health education. Conclusion: The higher prevalence of overweight and obesity in this young age range necessitates immediate attention to prevention and control. Obesity has been linked to an increased risk of a variety of ailments, and becoming aware of this is the first step toward taking preventative measures. While medical students exhibit a high level of awareness regarding major complications of obesity, they should also receive health education regarding other complications. This study is significant for the scientific community due to its focus on perceptions of obesity among female medical students in South India. It provides crucial insights into the prevalence of overweight and obesity, as well as awareness of associated risks among future healthcare professionals.